2002
DOI: 10.1034/j.1600-0668.2002.01145.x
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation and health in non-industrial indoor environments: report from a European Multidisciplinary Scientific Consensus Meeting (EUROVEN)

Abstract: Scientific literature on the effects of ventilation on health, comfort, and productivity in non-industrial indoor environments (offices, schools, homes, etc.) has been reviewed by a multidisciplinary group of European scientists, called EUROVEN, with expertise in medicine, epidemiology, toxicology, and engineering. The group reviewed 105 papers published in peer-reviewed scientific journals and judged 30 as conclusive, providing sufficient information on ventilation, health effects, data processing, and report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
188
1
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(209 citation statements)
references
References 95 publications
12
188
1
8
Order By: Relevance
“…In England, 37 naturally ventilated houses that were built since 1995 had a ventilation rate between 0.17 h -1 and 0.51 h -1 (Crump et al, 2005). In European schools, the values of ventilation rates seem to be higher than those reported in this study (Wargocki et al 2002). For instance, Smedje et al (2000) reported rates in Swedish schools having an average around 3 h -1…”
Section: Exfiltration and Ventilation Ratecontrasting
confidence: 71%
“…In England, 37 naturally ventilated houses that were built since 1995 had a ventilation rate between 0.17 h -1 and 0.51 h -1 (Crump et al, 2005). In European schools, the values of ventilation rates seem to be higher than those reported in this study (Wargocki et al 2002). For instance, Smedje et al (2000) reported rates in Swedish schools having an average around 3 h -1…”
Section: Exfiltration and Ventilation Ratecontrasting
confidence: 71%
“…A number of prior studies have reported associations between lower building VRs (or higher CO2 concentrations used as a surrogate for VRs) and increased health-related outcomes, including building-related symptoms in offices (Erdmann and Apte 2004;Seppanen et al 1999;Wargocki et al 2002); febrile respiratory illness in barracks (Brundage et al 1988); respiratory infections in dormitories (Sun et al 2011); and respiratory symptoms and nasal patency in school classrooms (Simoni et al 2011). Other studies have found associations between lower VRs and increased absence metrics in offices, used as indicators of health outcomes.…”
Section: Ventilation Rates and Healthmentioning
confidence: 99%
“…In comparison with balanced ventilation or supply and exhaust ventilation, the proportion of exhaust ventilation has been around 60% since 2001 (Svensk Fjärrvärme AB 2009). Some studies have concluded that fewer health related problems were reported in buildings with exhaust ventilation (Wargocki et al 2002).…”
Section: Introductionmentioning
confidence: 99%